Breast Cancer Integrative Oncology Care and Its Costs. (March 2017) - Standish, Leanna J.; Dowd, Fred; Sweet, Erin; Dale, Linda; Weaver, Morgan; Osborne, Barbara; Andersen, M. Robyn
Background. Naturopathic oncology in conjunction with conventional treatment is commonly referred to as integrative oncology (IO). Clinics directed by oncology board certified NDs (Fellows of the American Board of Naturopathic Oncology or FABNOs) provide high-quality data for describing IO therapies, their costs and measuring clinical outcomes. Purpose. To describe the types of IO therapies prescribed to breast cancer patients by ND FABNO physicians. Study participants (n = 324). Women who sought care at 1 of 6 naturopathic oncology clinics in Washington State were asked to enroll in a prospective 5 year observational outcomes study. Methods. Medical records were abstracted to collect treatment recommendations and cost data. Results. More than 72 oral or topical, nutritional, botanical, fungal and bacterial-based medicines were prescribed to the cohort during their first year of IO care. Trametes versicolor was prescribed to 63% of the women. Mind-body therapy was recommended to 45% of patients, and 49% received acupuncture. Also, 26% were prescribed injectable therapy, including mistletoe, vitamin B complex (12%), IV ascorbate (12%), IV artesunate (7%), and IV nutrition and hydration (4%). Costs ranged from 1594/year for early-stage breast cancer to 6200/year for stage 4 breast cancer patients. Of the total amount billed for IO care for 1 year for breast cancer patients, 21% was out-of-pocket. Conclusions. IO care for women with breast cancer consists of botanical and mushroom oral therapies, parenteral botanical and nutrient therapy, mind-body medicine and acupuncture. IO clinic visits and acupuncture are partially paid for by medical insurance companies.